Deskripsi Kemampuan Pemecahan Masalah Matematis Berbasis Kontekstual Pada Peserta Didik Kelas IV SD Kartika XVII-1 Pontianak - Dewi, Yeti Kurnia; Bistari, Bistari; Salimi, Asmayani (AS-SABIQUN, 2023)
The need for this research stems from the gap between the ability of contextually based mathematical problem solving that will be attained and the poor ability of contextually based mathematical problem solving among students in schools. This research attempts to describe how well fourth graders at SD Kartika XVII-1 Pontianak are able to solve mathematics problems based on contextually broad material. Descriptive research methodology is employed. Six students were chosen as the sample for this investigation based on preset criteria. Measurements and interviews are the data gathering methods used in this investigation. Test and interview guidelines served as the research instruments. Test and interview data analysis techniques are employed in data analysis. The research findings show that students can solve contextually based problems 46.57% of the time, comprehend contextually based problems 54.38% of the time, create contextually based problem-solving plans 57.89% of the time, execute contextually based problem-solving plans 40.35% of the time, and reassess contextually 32.89% of the time. Based on the results, it can be said that students' contextual-based mathematical problem-solving abilities fall into the moderate category, with the capacity to construct contextually-based solutions plans serving as both an indicator of majority ability and an indicator of minority ability. is the capability of contextually based re-selection.